Who said fear? (Journal of Parents and Teachers, 2014)
Making classifications of fears can be a never ending activity because every person is different and unrepeatable. Fear to rejection, to the unknown, to lose what we love and to failure are the most common ones. But the origin of fear is actually in our personal stories linked to episodes of our past. Therefore, answers to fear: negation, paralysation, and intervention help to get over fears.
Keywords: fear; values; psychology